Cognitive abilities related to foraging behavior in Vespula vulgaris (Hymenoptera: Vespidae) - Manattini, María Celeste (2024)
Vespula vulgaris is an invasive social wasp that has become established in many parts of the world. Plastic cognitive systems are expected to be advantageous for invasive species, given that they continuously face dynamic and unpredictable environments. We analyzed foraging behavior associated with undepleted and depleted resources. The wasps were trained to associate a certain location with food and we recorded their behavior after successive displacement of it. We also studied how long wasps continued to search for food that was no longer available and whether it was dependent on experience. We found that when wasps associated a certain location with food, they returned to the same site even though food was no longer available or had been displaced. Handling time remained constant, while relocation time and learning flights decreased with experience. With a food position change, learning flights increased and searching time varied with experience. When food was removed, hovering and landings were greatest in wasps that had the most experience with the resource, although extinction of the searching response was not dependent on experience. Our results illustrate the plasticity of wasp behavior in uncertain foraging contexts, which could have allowed the species to establish successfully in new habitats.